Assessing of the potential of extruded flour paste as fat replacer in O/W emulsion: A rheological and microstructural study. (August 2015) - Román, Laura; Martínez, Mario M.; Gómez, Manuel
Abstract: Extruded flour represents an economical and environmental friendly alternative as fat replacer. In this research, the potential use of an extruded flour–water paste as fat replacer in an oil-in-water emulsion was studied. The effect of flour–water ratio and level of oil replacement (30, 50 and 70%) on the microstructure, rheological properties and stability of mayonnaise-like emulsion was evaluated. Fat replacement by extruded flour gradually increased the number and reduced the size of oil droplets. All the emulsion samples showed a pseudoplastic behaviour. At low shear rates a Newtonian region characterised by Carreau model appeared (R 2  > 0.99). In general, the limiting viscosity of the Newtonian region and the consistency index increased with the decreased water content of the paste and increased the level of oil substitution. A decrease in oil concentration led to a greater thixotropic behaviour. Oscillatory test revealed that predominance of the continuous or dispersed phase influenced viscoelastic behaviour. Reduction in oil content resulted in an increased freeze–thaw stability. Results suggested that if the flour–water ratio of the paste is controlled, extruded flour is appropriate for preparing reduced-fat oil-in-water emulsion with similar rheological properties to the full fat and greater freeze–thaw stability. Highlights: Reduced-fat mayonnaises were elaborated with an extruded flour paste as oil replacer. Oil replacement gradually increased the number and decreased the size of oil droplets. Oil replacement gradually increased the thixotropic behaviour. Predominance of the continuous or dispersed phase affected viscoelastic behaviour. Reduced-fat mayonnaises are more adequate to their application in frozen foods.